24 vs. 72 hours of hypothermia for pediatric cardiac arrest: A pilot, randomized controlled trial. (May 2018) - Fink, Ericka L.; Clark, Robert S.B.; Berger, Rachel P.; Fabio, Anthony; Angus, Derek C.; Watson, R. Scott; Gianakas, John J.; Panigrahy, Ashok; Callaway, Clifton W.; Bell, Michael J.; Kochanek, Patrick M.
Abstract: Aim: Children surviving cardiac arrest (CA) lack proven neuroprotective therapies. The role of biomarkers in assessing response to interventions is unknown. We hypothesized that 72 versus 24 h of hypothermia (HT) would produce more favorable biomarker profiles after pediatric CA. Methods: This single center pilot randomized trial tested HT (33 ± 1 °C) for 24 vs. 72 h in 34 children with CA. Children comatose after return of circulation aged 1 week to 17 years and treated with HT by their physician were eligible. Serum was collected twice daily on days 1–4 and once on day 7. Mortality was assessed at 6 months. Results: Patient characteristics, baseline biomarker concentrations, and adverse events were similar between groups. Eight (47%) and 4 (24%) children died in the 24 h and 72 h groups, p = .3. Serum neuron specific enolase (NSE) concentration was increased in the 24 vs. 72 h group at 84 h–96 h (median [interquartile range] 47.7 [3.9, 79.9] vs. 1.4 [0.0, 11.1] ng/ml, p = .02) and on day 7 (18.2 [3.2, 74.0] vs. 2.6 [0.0, 12.8] ng/ml, p = .047). Serum S100b was increased in the 24 h vs. 72 h group at 12 h–24 h, 36 h–84 h, and on day 7, all p < 0.05. HT duration was associated with S100b (but not NSE or MBP) concentration on day 7 in multivariate analyses. Conclusion: Serum biomarkers show promise as theragnostic tools in pediatric CA. Our biomarker and safety data also suggest that 72 h duration after pediatric CA warrants additional exploration.